Peran Operator Maintenance dalam Menjaga Kondisi Forklift - Rafi Abdullah Shall; Andri Wibisono; Danny Irawan; Dhika Pangestu; Dwi Irmawati (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Modern industrial activities rely heavily on tools such as forklifts in the process of moving materials. However, the use of forklifts that are not accompanied by optimal maintenance can increase the risk of work accidents and disrupt smooth operations. This study aims to examine the role of maintenance operators in maintaining the condition of forklifts so that they remain optimal and safe to use. The method used is a descriptive qualitative approach with data collection through literature study and field observation. The results showed that maintenance operators play an important role not only in operating forklifts, but also in daily inspection (P2H), early detection of damage, and implementation of light maintenance (autonomous maintenance). The effectiveness of this role is influenced by technical training, compliance with SOPs, availability of P2H forms, and management support. The active role of operators has been shown to reduce defects, minimise downtime, and improve work safety and operational efficiency. This study recommends regular training, digitisation of inspection processes, and close collaboration between operators and technicians as strategies to improve maintenance performance.